Patterson, Isabel (audio interview #1 of 1) - Patterson, Isabel (11/27/1907 - 5/9/1996); Cleary, Cindy, interviewer
INTERVIEW DESCRIPTION - This single interview was conducted in Isabel Patterson's home and she expressed delight that the interviewer's child was enrolled in the Isabel Patterson Child Development center. The audio quality of this interview is good. 2/7/1979